Bio-inputs: An Alternative to Achieve Sustainable Agriculture - Rosales-Castillo, Rocio; Velázquez-de Lucio, Brianda Susana; Hernández-Domínguez, Edna María; Álvarez-Cervantes, Jorge (REVISTA TERRA LATINOAMERICANA, 2025)
Agriculture involves the cultivation and domestication of plants, but dif ferent agricultural practices worldwide have led to the intensive use of natural resources, synthetic fertilizers and pesticides, as well as the use of heavy machinery and irrigation technologies. This has had negative consequences, mainly through the reduction of biodiversity, the appearance of resistant pests, imbalances in agroecosystems and harmful environmental ef fects. In view of this, research has focused on sustainable agriculture, whose production is economically, socially and environmentally acceptable. To achieve this, the application of bio-inputs formulated with biotechnological techniques from microorganisms, plants, compounds and extracts thereof, capable of improving crop yield and health, has been proposed. Therefore, the objective of this chapter is to show the advances in the production of bio-inputs, their characteristics and application results since they can gradually replace the use of synthetic inputs, reducing the pollutants generated by this sector, in addition to taking advantage of waste from various sectors to incorporate them into the circular economy. It is necessary to continue with research to integrate potential species in the formulation of bioproducts and to deepen in metaomics and bioinformatics with impact and improvement of agricultural activities.